Fatty Acids 2017
DOI: 10.5772/intechopen.68440
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acids in Veterinary Medicine and Research

Abstract: Faty acid regulation is an essential process for all animals. A number of studies have shown that diet afects the levels/availability of faty acids in the body but increasingly an evidence shows that disease states can alter the amounts within the body too. Faty acid levels and availability have been altered by a number of diseases, disorders and reactions including inlammatory responses, heart disease and heart failure and wound repair. They are also essential during the growth and development stages of anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 143 publications
(160 reference statements)
0
3
0
Order By: Relevance
“…5 Total PUFA = %C18:2 + %C20:3 + %C20:4 + %C22:5 + %C20:5 + %C22:6. 6 SFA/MUFA = (%C14:0 + %C16:0 + %C18:0)/(%C16:1 + %9c,C18:1 + %11c,C18:1). 7 Omega-6/omega-3 ratio = (%C18:2 + %C20:3 + %C20:4 + %C22:5)/(%C20:5 + %C22:6.).…”
Section: The Erythrocyte Membrane Lipidome In Healthy Donkeysmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Total PUFA = %C18:2 + %C20:3 + %C20:4 + %C22:5 + %C20:5 + %C22:6. 6 SFA/MUFA = (%C14:0 + %C16:0 + %C18:0)/(%C16:1 + %9c,C18:1 + %11c,C18:1). 7 Omega-6/omega-3 ratio = (%C18:2 + %C20:3 + %C20:4 + %C22:5)/(%C20:5 + %C22:6.).…”
Section: The Erythrocyte Membrane Lipidome In Healthy Donkeysmentioning
confidence: 99%
“…It has been demonstrated that fatty acids play a crucial role on the health status of all living organisms, both human and animals [6], with the erythrocyte membrane fatty acid content being the main subject of research in animals through the last years [7,8]. A previous study showed that an altered lipid metabolism can result in the development of metabolic syndrome in equids [9].…”
Section: Introductionmentioning
confidence: 99%
“…Limited studies presented a small number of samples (35,36), focusing for example on PUFA (omega-6 and omega-3), and not deepening the different fatty acid families, which are instead important for molecular contribution to membrane homeostasis (37). Although fatty acids are recognized to be crucial for all animals (38), an effort to build up the methodology for fatty-acidbased membrane lipidomics in the veterinary field is missing. In the present work, we evaluated the composition of fatty acids in erythrocyte membrane phospholipids in a group of clinically healthy dogs (n = 68), focusing on the interval ranges of the 10 fatty acid cohort previously used for humans.…”
Section: Introductionmentioning
confidence: 99%